2005
DOI: 10.1111/j.1742-4658.2005.04612.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of raft‐like domains by a myristoylated NAP‐22 peptide and its Tyr mutant

Abstract: The N‐terminally myristoylated, 19‐amino acid peptide, corresponding to the amino terminus of the neuronal protein NAP‐22 (NAP‐22 peptide) is a naturally occurring peptide that had been shown by fluorescence to cause the sequestering of a Bodipy‐labeled PtdIns(4,5)P2 in a cholesterol‐dependent manner. The present work, using differential scanning calorimetry (DSC), extends the observation that formation of a PtdIns(4,5)P2‐rich domain is cholesterol dependent and shows that it also leads to the formation of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 48 publications
(81 reference statements)
2
27
0
Order By: Relevance
“…The ability of NAP-22 to influence the distribution of PtdIns(4,5)P 2 and cholesterol in membranes provides a mechanism by which this protein can influence the actin cytoskeleton (Epand et al, 2003a(Epand et al, ,b, 2001(Epand et al, , 2004. Since NAP-22 sequesters both cholesterol and PtdIns(4,5)P 2 into domains, it has been suggested that the protein recruits PtdIns(4,5)P 2 into raft-like domains and increases cytoskeleton/plasma membrane interactions through rafts that induce spatial rearrangements of the cytoskeleton (Epand et al, 2005a). In a bilayer that phase-segregates into l o (enriched in Chol and SM) and DOPC-enriched (l d ) domains, it was found that the fulllength NAP-22 inserts almost exclusively into the l o domain (Khan et al, 2003).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The ability of NAP-22 to influence the distribution of PtdIns(4,5)P 2 and cholesterol in membranes provides a mechanism by which this protein can influence the actin cytoskeleton (Epand et al, 2003a(Epand et al, ,b, 2001(Epand et al, , 2004. Since NAP-22 sequesters both cholesterol and PtdIns(4,5)P 2 into domains, it has been suggested that the protein recruits PtdIns(4,5)P 2 into raft-like domains and increases cytoskeleton/plasma membrane interactions through rafts that induce spatial rearrangements of the cytoskeleton (Epand et al, 2005a). In a bilayer that phase-segregates into l o (enriched in Chol and SM) and DOPC-enriched (l d ) domains, it was found that the fulllength NAP-22 inserts almost exclusively into the l o domain (Khan et al, 2003).…”
Section: Discussionmentioning
confidence: 97%
“…Inset: corresponding section analyses along A-A 0 . PtdIns(4,5)P 2 (Epand et al, 2005a(Epand et al, ,c, 2004. As the NAP-22 peptide concentration increases in the l d domain, it is likely that the peptide would start to recruit more cholesterol from the SM/Chol domain.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Myristate inserts hydrophobically into the lipid bilayer whereas basic amino acids form electrostatic interactions with the headgroups of acidic membrane phospholipids including PI (4,5)P 2 . There is evidence that in resting cells PI (4,5)P 2 is sequestered in cholesterol-rich domains by interaction with the hydrophobic/ basic motif of myristoylated proteins such as MARCKS, NAP-22, CAP-23, GAP-43 (Laux et al, 2000;Epand et al, 2005;McLaughlin & Murray, 2005). The modulation of availability of free PI (4,5)P 2 by these proteins regulates a number of cell signaling cascades in cells.…”
mentioning
confidence: 99%